RISET NON POSITIVISTIK AKUNTANSI DALAM TIGA PARADIGMA: INTERPRETIF, KRITIS DAN POSMODERNISME - Paranoan, Natalia (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 1 (2015))
Non positivistik research methodology has been progressing very rapidly. However, the perception of most people still consider that this study as research with nonmatematik procedure, make meaning (rather than empirical analysis) on qualitative data based on the results of the study according to the grass root. Now a new vision, a new paradigm and a new perspective began to flourish in non positivistic research. Charasteristics of the new dominant is: critically on existing paradigms and evolving conceptualization, understanding and giving the meaning of the truth of the future. Of which have emerged and grown at least a critical attitude towards the old vision. With this latest growth, prestige positivism philosophy that permeates the tradition of social science and humanities development since the nineteenth century to fade. This article discusses the nonpositivistic research in three paradigms; interpretive, critical and postmodern as well as the implications for accounting research in the future.
Keywords: positivist, interpretive, critical, postmodern